The Inflammatory Response to Enterotoxigenic E. coli and Probiotic E. faecium in a Coculture Model of Porcine Intestinal Epithelial and Dendritic Cells. (20th December 2018) - Loss, Henriette; Aschenbach, Jörg R.; Tedin, Karsten; Ebner, Friederike; Lodemann, Ulrike
Abstract : The gut epithelium constitutes an interface between the intestinal contents and the underlying gut-associated lymphoid tissue (GALT) including dendritic cells (DC). Interactions of intestinal epithelial cells (IEC) and resident DC are characterized by bidirectional crosstalk mediated by various factors, such as transforming growth factor- β (TGF- β ) and thymic stromal lymphopoietin (TSLP). In the present study, we aimed (1) to model the interplay of both cell types in a porcine in vitro coculture consisting of IEC (cell line IPEC-J2) and monocyte-derived DC (MoDC) and (2) to assess whether immune responses to bacteria are altered because of the interplay between IPEC-J2 cells and MoDC. With regard to the latter, we focused on the inflammasome pathway. Here, we propose caspase-13 as a promising candidate for the noncanonical inflammasome activation in pigs. We conducted challenge experiments with enterotoxigenic Escherichia coli (ETEC) and probiotic Enterococcus faecium ( E. faecium ) NCIMB 10415. As potential mediators of IEC/DC interactions, TGF- β and TSLP were selected for analyses. Cocultured MoDC showed attenuated ETEC-induced inflammasome-related and proinflammatory interleukin (IL)-8 reactions compared with MoDC monocultures. Caspase-13 was more strongly expressed in IPEC-J2 cells cocultured with MoDC and upon ETEC incubation. We found that IPEC-J2 cells and MoDC were capable of releasing TSLP. The latter cells secreted greater amounts of TSLP when cocultured with IPEC-J2 cells. TGF- β was not modulated under the present experimental conditions in either cell types. We conclude that, in the presence of IPEC-J2 cells, porcine MoDC exhibited a more tolerogenic phenotype, which might be partially regulated by autocrine TSLP production. Noncanonical inflammasome signaling appeared to be modulated in IPEC-J2 cells. Our results indicate that the reciprocal interplay of the intestinal epithelium and GALT is essential for promoting balanced immune responses.